Add Simplify if possible

9x/x^2-4 + x/x-2

1 answer

I am sure you meant

9x/(x^2 - 4) + x/(x-2)

= 9x/((x+2)(x-2)) + x/(x-2) , LCD = (x+2)(x-2)
= 9x/((x-2)(x+2)) + x(x+2)/((x+2)(x-2))
= (9x + x^2 + 2x)/(x^2 - 4)
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions